Gastric mucosal hyperplasia via upregulation of gastrin induced by persistent activation of gastric innate immunity in major histocompatibility complex class II deficient mice. Issue 5 (1st December 2005) - Fukui, T; Nishio, A; Okazaki, K; Uza, N; Ueno, S; Kido, M; Inoue, S; Kitamura, H; Kiriya, K; Ohashi, S; Asada, M; Tamaki, H; et al.
Abstract : Background and aim: Major histocompatibility complex class II deficient (Aα 0/0 ) mice have decreased CD4 + T cells, making them immunologically similar to patients with acquired immunodeficiency syndrome (AIDS). Both patients with AIDS and Aα 0/0 mice have hypertrophic gastric folds. To clarify the mechanism of gastric mucosal hyperplasia, we investigated the pathophysiology and the role of the innate immunity in the stomach of Aα 0/0 mice. Methods: Stomachs from 1–6 month old Aα 0/0 mice, kept under specific pathogen free conditions, were examined at 1 month intervals histologically and immunohistochemically. Gene expression of proinflammatory cytokines, Toll-like receptors (TLRs), cyclooxygenase (COX)-2, and myeloperoxidase (MPO) activity in the gastric mucosa was investigated. Serum gastrin levels and gastric acidity were measured. Bacterial culture of the stomach was performed. To clarify the roles of hypergastrinaemia in the gastric mucosa, a gastrin receptor antagonist (AG041R) was administered. Results: Aα 0/0 mice had a diffusely thick corpus mucosa with infiltration of CD11b + granulocytes and macrophages. Anti-Ki67 staining demonstrated expansion of the proliferating neck zone. Gene expression of interleukin 1β, interferon γ, TLR-2, TLR-4, and COX-2 were upregulated, and MPO activity was increased. Only a small amount of non-pathogenic bacteria was detected in the stomach. Serum gastrin levels and Reg-Iα positive cells in the gastric mucosa increased, despite normal gastric acidity. After treatment with AG041R, gastric mucosal thickness was significantly reduced. Conclusion: Persistent activation of innate immunity in the stomach induced gastric mucosal hyperplasia through upregulation of gastrin synthesis in Aα 0/0 mice, suggesting a pathophysiology similar to the gastric changes in patients with AIDS.